Lifting Health Professionals’ Morale During the COVID-19 Pandemic: Moderating Emotions to Support Ethical Decisions - Blasco, Pablo; de Benedetto, Maria; Levites, Marcelo; Moreto, Graziela (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2021)
The current COVID-19 pandemic creates a difficult and unprecedented time. With each passing day, the care of the health team itself is essential; and not only physical care, but also for mental health. The authors describe their experience in disseminating recommendations through short videos to help professionals maintain an objective view of the reality they are experiencing. Thus, knowing how to tabulate daily the evolution of the patients that each professional has been entrusted to care for – the hospitalized, the deaths and, very importantly, the discharge of the recovered – provides a sense of reality. Cinema, an educational resource used in medical education, which is also included in these videos, helps to clarify the recommendations made above and to maintain emotional balance. The authors conclude that providing a realistic view of the situation that the team is experiencing in this crisis and highlighting the positive facts and achievements could be a valuable means of help from medical educators behind the scenes.